(untitled) (Revista de História da UEG (REVHIST), 2025)
The 20th century was a time of great transformation in history. New paradigms allowed previously ignored subjects and social groups to become historical agents. Problem history, together with the methodology of the New Cultural History (NCH), included new historical sources and approaches. This article presents an investigation into the interaction between history and music, more specifically its capacity for historical representation. Through the song Ethiopia, composed and performed by the Cachoeiran reggaeman Edson Gomes, I discuss the way in which the Second Italo-Ethiopian War (1935-1936) was represented. To support the analysis, I review the history of reggae and its insertion in Bahia, as well as the historical context involving hostilities between Italians and Ethiopians dating back to the end of the 19th century. Keywords: Edson Gomes; Ethiopia; History and Music; Reggae; Historical representation.